2012
DOI: 10.1155/2012/917346
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile of Patients with Cutaneous Melanoma in a Region of Southern Brazil

Abstract: Cutaneous melanoma (CM) is responsible for 75% of deaths from malignant skin cancer. The incidence of CM in the southern region of Brazil, particularly in the western region of Santa Catarina, is possibly higher than estimated. In this study, the clinical and epidemiological profile of patients with CM treated in the western region of Santa Catarina was examined. A cross-sectional study was performed with patients diagnosed with CM from January 2002 to December 2009, from 78 counties of the western region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
34

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 33 publications
1
13
0
34
Order By: Relevance
“…In line with results from other studies in several geographic areas [21,[33][34][35], we observed a significant association between gender and Breslow: males diagnosed with a higher proportion of melanomas with Breslow over 4 mm. These differences between Breslow according to sex and age could be explained by an improvement in self-examination and different habits in young and female individuals [36,37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with results from other studies in several geographic areas [21,[33][34][35], we observed a significant association between gender and Breslow: males diagnosed with a higher proportion of melanomas with Breslow over 4 mm. These differences between Breslow according to sex and age could be explained by an improvement in self-examination and different habits in young and female individuals [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…According to the Globocan Project, skin melanoma mortality rates in South America, estimated for 2018, were 0.60/100,000 for females and 1.2/100.000 for males [3]. In Brazil, melanoma mortality differed by regions: 0.26/100,000 in the North; 0.35 in the North East; 0.90 in the South East; 1.74 in the South and 0.64 in the Midwest [33]. Also, in Chile and in Colombia, mortality rates varied along the country [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, they are characterized by an increased number of normal dendritic melanocytes along the dermo-epidermal junction. The solar lentigo appears on sun-exposed surfaces during middle to late life, in common with lentigo maligna, and may closely resemble lentigo maligna [87,94,102].…”
Section: Lentigo Maligna and Lentigo Maligna Melanomamentioning
confidence: 99%
“…Between 2002 and 2009, the prevalence was 71.5 cases per 100,000 inhabitants. In 2008, the incidence was 12.2 cases per 100,000 inhabitants [14]. Brazil has also experienced an increase in CMrelated mortality, especially in certain areas of the country [12,13].…”
Section: Introductionmentioning
confidence: 99%